TiO2 enrichment in ocean island basalts - Prytulak, J; Elliott, T (2007)
An extensive dataset of ocean island basalt (OIB) compositions highlight that their titanium (Ti) contents are generally too high to be derived from melting of a peridotitic mantle. Even vanishingly small degree melts of a primitive mantle source have insufficient Ti to reproduce the compositions of many OIB. A Ti-enriched material is thus a necessary additive to many OIB sources. Of the enriched components commonly invoked to explain the range in OIB radiogenic isotopic signatures, only the addition of small amounts (∼ 1-10%) of recycled mafic crust is compatible with all geochemical constraints. Since such mafic crust starts melting deeper than its host peridotite, small degree melts formed beneath thick lithosphere will preferentially sample this enriched heterogeneity. This is compatible with the observation that the most Ti rich OIB also have the most enriched and variable signatures in terms of radiogenic isotope ratios. However, recycled mafic crust itself is insufficiently extreme isotopically to be able to account for the full range of isotopic ratios in OIB, therefore further, associated components (e.g. sediments, metasomatic veins) seem necessary in some cases. © 2007 Elsevier B.V. All rights reserved.